Mapping the nation - Balakrishnan, Gopal (Verso, 1996)
Few political phenomena have proved as confusing and difficult to comprehend as nationalism. There is no consensus on its identity, genesis or future. Are we, for example, in the process of being thrust back into a nineteenth-century world of competitive and aggressive great powers and petty nationalisms? Or are we being flung headlong into a new, globalized and supra-national millennium? Has the nation-state outlived its usefulness and exhausted its progressive and emancipatory role, or has nationalism always been implicated in an exclusivist ethnic and militaristic logic? Mapping the Nation seeks to address these and other questions about the nature and destiny of the 'national question' in the present epoch. A comprehensive and definitive reader on the subject, with contributions from some of the most significant and stimulating theorists of the nation-state, it presents a wide range of divergent ideas and controversies. Leading off with powerful statements of the classic liberal and socialist positions, by Lord Acton and Otto Bauer, there then follows an historical-sociological debate between the late Ernest Gellner and the Czech historian Miroslav Hroch, the one stressing the connections between nationalism and the transition away from agrarian society, the other emphasizing its variability and real anthropological basis. John Breuilly and Anthony D. Smith, two of the leading British specialists, provide a counterpoint to each other with considerations on the respective importance of political leadership and continuing ethnic communities in the construction of nationalist movements. Gopal Balakrishnan, in a carefully honed critique of Benedict Anderson's seminal Imagined Communities, and Partha Chatterjee, from the Subaltern Studies circle, offer crucial insights on the limitations of the Enlightenment approach to nationhood, as do Sylvia Walby and Katherine Verdery with their reflections on the entanglements of nation, gender and identity politics. Sociologist Michael Mann delivers an authoritative refutation of the chatter about the 'death of the nation-state'. Finally, relating the theoretical questions directly to the politics of our time, renowned historian Eric Hobsbawm, provocative theorist Tome Nairn, and the outstanding political philosopher Jurgen Habermas discuss, with varying degrees and pessimism, the future of the national project.